Clinical significance of HER2 overexpression in biliary tract carcinoma ——a meta analysis - Xu, Haonan; Liang, Yuwen; Tang, Wenqiang; Yang, Xiongxin; Du, Xiaobo (Frontiers in Oncology, 2025)
IntroductionPrevious studies have been inconsistent on the correlation of human epidermal growth factor receptor 2 (HER2) overexpression in biliary tract carcinoma. The objective of this meta analysis was to assess its association with clinicopathological features and prognostic significance of biliary tract carcinoma.MethodsThe eligible studies were searched in Pubmed, Embase and Web of Science databases. Inclusion criteria were studies of the relationship between HER2 positive expression (ICH: HER2 (+++), FISH: HER2 overexpression, NGS: HER2 overexpression) and prognosis or clinicopathological features of patients with biliary tract carcinoma (BTC). The analysis was conducted according to gender, high differentiation degree, middle differentiation degree, tumor stage, nerve invasion, vascular invasion, lymph node metastasis and pathological diagnosis of patients. ES (Effect Sizes) for 95% confidence intervals (CI) were calculated to examine risk or hazard associations, and heterogeneity and sensitivity analyses were performed.ResultsA total of 15 studies were included to evaluate the association of HER2 positive expression with clinicopathological features and survival prognosis. There was no significant statistical relationship between positive/high expression of HER2 and a series of clinical characteristics including gender, high, middle and low differentiation, tumor stage, vascular invasion, nerve invasion, Lymph node metastasis, T stage and pathological type of patients with biliary tract carcinoma. There was a significant relationship between positive/high expression of HER2 and postoperative Disease-Free Survival in patients with biliary tract carcinoma (ES = 1.87, 95% CI: 1.24-2.81, p = 0.003). There was a significant relationship between positive/high expression of HER2 and postoperative Overall Survival in patients with biliary tract carcinoma (ES = 1.54, 95% CI: 1.08-2.20, p = 0.017).DiscussionOur meta-analyses revealed that high expression of HER2 gene was not correlated with clinicopathological parameters such as differentiation degree, TNM stage, lymph node metastasis, vascular invasion, nerve invasion, pathological type, T stage, and gender of biliary tract carcinoma. HER2 overexpression is a negative prognostic factor in biliary tract carcinoma patients. The association between positive/high expression of HER2 and the pathological features as well as prognosis in biliary tract carcinoma patients warrants further validation.